The United States and Right-Wing Dictatorships, 1965–1989 - Schmitz, David F (Cambridge University Press, 2013)
Since its founding, the United States has been philosophically dedicated to supporting liberal democracy and the rule of law. This commitment is found in the most important documents and treaties of the nation, including the Declaration of Independence, the Constitution, and the United Nations Universal Declaration of Human Rights, and has been proclaimed by presidents, secretaries of state, and other policymakers from the time of George Washington to the present day